Rękojmia za wady produktów rolnych - Blajer, Paweł (Wydawnictwo Naukowe UAM, 2009)
The aim of the paper is to elaborate the answer to the question whether traditional, civilistic institution of warranty against product flaws responds to contemporary circumstances under which the market in agricultural products functions. Further on, the purpose of the article is to find out whether specific regulation of the civil code on the warranty of certain agricultural products makes it possible to formulate a separate, agricultural law institution to be named “agricultural warranty”. Because then, it might be the subject of interest for agricultural law and not for the civil law. The author analyses the civil code regulations and compares the warranty institution with other liability regimes an agricultural producer may be subject to. The author concludes by noting the specificity of agricultural product warranty, but available arguments are insufficient to treat it as agricultural warranty. Currently, agricultural product warranty is only one of several other liability regimes an agricultural producer should reckon with. Besides, it seems that the meaning o f this institution is gradually decreasing.

L’obiettivo dell’autore e quello di dare una risposta alia domanda se l’istituto del pegno per difetti risponde alle attuali esigenze del mercato dei prodotti agricoli, nonche di stabilire se le regolazioni specifiche contenute nel codice civile concementi il pegno per difetti di alcuni prodotti agricoli rendono possibilie la formulazione di un distinto istituto giuridico agrario, che potrebbe essere chiamato ,,il pegno agrario”, e che costituirebbe oggetto non gia del diritto civile, ma del diritto agrario. L’autore espone la disciplina del codice civile, analizzando anche i regimi di responsabilita ai quali puó essere sottoposto il produttore agricolo. In conclusione l’autore nota la specificita del pegno per difetti dei prodotti agricoli, ma osserva che mancano argomenti sufficienti per considerarlo “pegno agricolo”. In conclusione si puó affermare che il pegno per difetti dei prodotti agricoli sta perdendo di importanza a causa della sua scarsa applicazione.
Agricultural product warranty
Il pegno per idifetti dei prodotti agricoli